Selective bone marrow involvement of lymphoplasmacytic cells secreting monoclonal IgA rheumatoid factor in a patient with Sjögren's syndrome and serum hyperviscosity. Issue 12 (December 1987) - Bergonzi, C; Merlini, G P; Morandi, S; Bianchini, E; Pavesi, F; Bellotti, V; Montecucco, C M; Ascari, E
Abstract : The clinical features and results of serological studies of a patient with Sjögren's syndrome, IgA kappa monoclonal gammopathy, and hyperviscosity syndrome are reported. The novel aspect of this case is the selective localisation to the bone marrow of lymphoplasmacytoid cells secreting IgA kappa morphologically identical to the cells infiltrating the salivary glands. The serum of the patient contained large amounts of immunoglobulin-anti-immunoglobulin immune complexes. By gel filtration chromatography it was shown that the immune complexes formed a peak of molecular weight 680 kilodaltons. The immune complexes were dissociable under acidic conditions. The immunoglobulin with rheumatoid activity was characterised as monoclonal IgA kappa protein. Treatment with plasmapheresis combined with immunosuppressive treatment with cyclophosphamide reduced the serum viscosity with concomitant clinical improvement.